Preserving intangible cultural heritage knowledge : a framework for tangible user interface in Malaysian Museums / Mohd Nasiruddin Abdul Aziz, Siti Norlizaiha Harun and Mohd Khairi Baharom - Mohd Nasiruddin, Abdul Aziz; Siti Norlizaiha, Harun; Mohd Khairi, Baharom (Universiti Teknologi MARA, Perak, 2017)
Digital media has become an appropriate technique for presenting the content of Intangible Cultural Heritage (ICH) to new generations. The technogenesis concept argued that the digital technologies and human practice in object form need to be integrated and co-evolved together. This research aims to make the ICH content for craftsmanship knowledge in museum stay relevant through an effective tangible user interface. This research covered three phases; interpretation, prototype, and evaluation. Throughout the contextual analysis of the literature reviews, this paper briefly discusses the conceptual framework in developing a prototype of tangible user interface specifically for ICH preservation in museum.